Tribalisme, Oligarki Kekuasaan dan Dinamika Politik Kekerabatan Dalam Jaringan Pondok Pesantren - Nurul Azizah (Tebuireng: Journal of Islamic Studies and Society, 2021)
Religious elites have an important role in the democratic system in Indonesia. The involvement of chairmen of Islamic boarding schools (pondok pesantren) in local elections in the context of local dynamics has spawned a network of oligarchic power and dynastic politics. There is an assumption that the participation of the elite of Islamic boarding schools in local politics is considered to be inevitable to the democratic process with the spread of corruption cases, and political nepotism. Actors in dynastic politics use famous figures from the pesantren’s family as a political tool to gain power. Power relations and patron-client relationships in Islamic boarding schools provide great benefits to ensure a candidate is elected in a local election. The purpose of this paper is to analyze the relation between power, oligarchy, and the politics of kinship of the elite boarding school in the dynamics of local politics. This article shows that dynastic politics undermined the pillars of Indonesian democracy. Factors that cause oligarchy in pondok pesantren are populism, power network, and tribalism. These factors are inseparable from the influence of patronage, the power of local elites, and the effort of the elite to build dynastic politics. This article suggests that religious elites within the circle of political dynasties are expected to work professionally, not merely using the pesantren family.